Risk propagation assessment for network security : application to airport communication network design - Ben Mahmoud, Mohamed Slim (ISTE ; Wiley, 2013)
The focus of this book is risk assessment methodologies for network architecture design. The main goal is to present and illustrate an innovative risk propagation-based quantitative assessment tool. This original approach aims to help network designers and security administrators to design and build more robust and secure network topologies. As an implementation case study, the authors consider an aeronautical network based on AeroMACS (Aeronautical Mobile Airport Communications System) technology. AeroMACS has been identified as the wireless access network for airport surface communication.- Resumé vydavatel
Keywords: počítačové sítě; zabezpečení počítačových sítí; letectví; komunikační systémy; síťová architektura; computer networks; computer network security; aviation; communication systems; computer network architecture; elektronické knihy; monografie; electronic books; monographs